Urgensi Perlindungan Data Pribadi Terhadap Pengguna dan Kontak Darurat dalam Transaksi Pinjaman Online - Sinaga, Rio Alfred; Widyaningrum, Tuti (Neolectura, 2025)
Currently the financial sector is facing a new model of technology so called fin-tech. Financial technology based on Peer to Peer Lending (P2PL-based Fintech) is one of the new breakthroughs in financial services institutions in Indonesia. The presence of P2PL-based Fintech is a solution for people who have not been touched by banking but have technology literacy. However P2PL not only give positive impact but also negative impact i.e it’s spread the privacy of data consumer to whom inresponsibilty. Therefore it is need to give legal protection to consumer. The aim of this paper is to examine the legal protection of borrowers' personal data in online loan application services. The method used in this paper is a normative legal method with a statutory approach and a factual approach. The results of the study show that legal protection for consumer has in Law No. 8 of 1999 on Consumer Protection, of 2008 OJK Regulation No. 1/POJK.07/2013 Tentang Perlindungan Konsumen Sektor Jasa Keuangan, Ministerial Regulation No. 20 of 2016 on Personal Data Protection within Electronic Systems however these regulations has not provide data privacy however these regulations are deemed insufficient in preventing large-scale data breaches.